2018
DOI: 10.1007/s00380-018-1147-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of an iatrogenic atrial septal defect after a second-generation cryoballoon ablation of atrial fibrillation

Abstract: Persistent iatrogenic atrial septal defects (iASDs) can be observed after intervention requiring a left atria (LA) access, including pulmonary vein isolation (PVI) of atrial fibrillation (AF). We investigated the incidence of iASDs post-second-generation cryoballoon ablation and the pre-procedural predictors. Eighty-three paroxysmal AF patients underwent PVI using second-generation cryoballoons. The LA was accessed with single 15-Fr steerable sheaths following a radiofrequency transseptal puncture, and the iAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Recently, Linhart et al [14] reported a relatively high incidence of ASD after CB PVI but without increased clinical complication. This is consistent with other groups’ findings concerning persistent ASD after CB or RF PVI [15], [16], [17]. We report on an evasion maneuver to facilitate transseptal access with the 12F CB sheath (15F outer lumen) in patients undergoing PVI.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Linhart et al [14] reported a relatively high incidence of ASD after CB PVI but without increased clinical complication. This is consistent with other groups’ findings concerning persistent ASD after CB or RF PVI [15], [16], [17]. We report on an evasion maneuver to facilitate transseptal access with the 12F CB sheath (15F outer lumen) in patients undergoing PVI.…”
Section: Discussionsupporting
confidence: 92%
“…Several case reports and series have been published describing the incidence and clinical implications of an iASD after PV isolation. [45][46][47][48][49][50][51][52] Within these series very few patients required closure of the iASD, suggesting that an iASD is generally benign. In the first report examining the incidence and outcome of iASD after cryoablation specifically, 4 of 13 patients had persistent iASD at 9 months and 1 required closure.…”
Section: Persistent Atrial Septal Defect Following Catheter Ablation mentioning
confidence: 82%
“…The defect usually presents with left-to-right shunt owing to the relatively higher left atrial pressure compared to the right atrial pressure but can also present with right-to-left shunt when there is underlying right heart failure or pulmonary hypertension. Several case reports and series have been published describing the incidence and clinical implications of an iASD after pulmonary vein isolation 1, 2, 3, 4, 5, 6, 7, 8. Within these series very few patients required closure of the iASD, suggesting that an iASD is generally benign.…”
Section: Discussionmentioning
confidence: 99%